2018
DOI: 10.1063/1.5025188
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing deceleration-phase instabilities in inertial confinement fusion implosions using an “enhanced self-emission” technique at the National Ignition Facility

Abstract: High-mode perturbations and low-mode asymmetries were measured in the deceleration phase of indirectly driven, deuterium gas filled inertial confinement fusion capsule implosions at convergence ratios of 10 to 15, using a new “enhanced emission” technique at the National Ignition Facility [E. M. Campbell et al., AIP Conf. Proc. 429, 3 (1998)]. In these experiments, a high spatial resolution Kirkpatrick-Baez microscope was used to image the x-ray emission from the inner surface of a high-density-carbon capsule'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…The origin of these perturbations (shown as 'meteors' in figure 14(b)) is currently not well understood and a subject of investigations by the indirect-drive program. In related experiments, the mode 1 asymmetry of the x-ray emission was correlated with the motion of the hot spot during peak compression [42]. These experiments also allowed studies of radiation-cooling effects on the neutron yield.…”
Section: 'Self-emission' Platform In the Deceleration Phasementioning
confidence: 94%
See 2 more Smart Citations
“…The origin of these perturbations (shown as 'meteors' in figure 14(b)) is currently not well understood and a subject of investigations by the indirect-drive program. In related experiments, the mode 1 asymmetry of the x-ray emission was correlated with the motion of the hot spot during peak compression [42]. These experiments also allowed studies of radiation-cooling effects on the neutron yield.…”
Section: 'Self-emission' Platform In the Deceleration Phasementioning
confidence: 94%
“…In another experiment (see figure 14(b)), a large number of the high-mode perturbations were detected in the implosion [43]. The origin of these perturbations (shown as 'meteors' in figure 14(b)) is currently not well understood and a subject of investigations by the indirect-drive program.…”
Section: 'Self-emission' Platform In the Deceleration Phasementioning
confidence: 99%
See 1 more Smart Citation
“…High resolution velocimetry measurements of the expansion of the rear surface of ablator materials has shown that perturbations may be seeded by the microstructure in crystalline materials such as beryllium and diamond [89] and is sensitive to both the crystalline structure and shock pressure. Efforts are underway to develop techniques that can measure mix at high convergence ratios (~10-20) related to the ablator/ice interfaces using x-ray self-emission backlighting [90,91], high resolution imaging with a spherical crystal imager [92], and cylindrical implosion platforms [93].…”
Section: High Mode Asymmetriesmentioning
confidence: 99%
“…So the high spatial resolution imaging diagnostics in a high X-ray energy band are necessary. Recently, the hydrodynamic instability growth radiography in the ICF [7,8] and some other high energy density physics (HEDP) experiments also employ more and more high resolution imaging diagnostics. The Kirkpatrick-Baez (KB) microscope is an advanced X-ray imaging system, with a high spatial resolution (several µm) and a high light collection efficiency (∼ 10 −7 ).…”
Section: Introductionmentioning
confidence: 99%